2020
DOI: 10.3389/fcell.2020.00558
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast-Derived Extracellular Vesicles Induce Colorectal Cancer Progression by Transmitting Amphiregulin

Abstract: Extracellular vesicles (EV), structures surrounded by a biological membrane, transport biologically active molecules, and represent a recently identified way of intercellular communication. Colorectal cancer (CRC), one of the most common cancer types in the Western countries, is composed of both tumor and stromal cells and the amount of stromal fibroblasts negatively correlates with patient survival. Here we show that normal colon fibroblasts (NCF) release EVs with a characteristic miRNA cargo profile when sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 47 publications
2
19
0
Order By: Relevance
“…Their sometimes opposing roles in lung cancer progression are indicated by studies showing that EVs modulated integrin trafficking in fibroblasts and enhanced tumor cell migration in NSCLC by carrying podocalyxin ( Novo et al, 2018 ), and they prevented metastatic angiogenesis in LUAD by transporting miR-192 ( Valencia et al, 2014 ). Similarly to CRC ( Szvicsek et al, 2019 ; Oszvald et al, 2020 ), we found that fibroblast-derived EVs induced cell proliferation both in bronchiolar and in LUAD organoids, thus proving the importance of fibroblast-derived EVs and that this mechanism is not restricted to CRC.…”
Section: Discussionsupporting
confidence: 54%
“…Their sometimes opposing roles in lung cancer progression are indicated by studies showing that EVs modulated integrin trafficking in fibroblasts and enhanced tumor cell migration in NSCLC by carrying podocalyxin ( Novo et al, 2018 ), and they prevented metastatic angiogenesis in LUAD by transporting miR-192 ( Valencia et al, 2014 ). Similarly to CRC ( Szvicsek et al, 2019 ; Oszvald et al, 2020 ), we found that fibroblast-derived EVs induced cell proliferation both in bronchiolar and in LUAD organoids, thus proving the importance of fibroblast-derived EVs and that this mechanism is not restricted to CRC.…”
Section: Discussionsupporting
confidence: 54%
“…Further, although the authors observed that normal colon fibroblasts (NCF) activated with TGFβ (one of the most important activating factors of fibroblasts) secrete EVs with a different miRNA content profile compared with controls (NCF not active with TGFβ), they did not find differences in the biological effects between the EVs treated and not treated with TGFβ, suggesting that TGFβ-induced sorting of specific miRNAs into EVs does not play a major role in enhancing CRC proliferation [291]. Thus, the authors provided evidence that amphiregulin, transported by EVs, is a major factor in inducing CRC proliferation [291].…”
Section: Future Prospects Of Cell-free Therapy For Cancer Treatment and Challenges To Be Overcomementioning
confidence: 95%
“…In this sense, using a 3D organoid model, Oszvald et al [291] showed that fibroblastderived EVs transporting amphiregulin (AREG) increase the number of proliferating colorectal cancer cells (CRC) in patient-derived organoid lines in an epidermal growth factor (EGF)-dependent manner. Further, although the authors observed that normal colon fibroblasts (NCF) activated with TGFβ (one of the most important activating factors of fibroblasts) secrete EVs with a different miRNA content profile compared with controls (NCF not active with TGFβ), they did not find differences in the biological effects between the EVs treated and not treated with TGFβ, suggesting that TGFβ-induced sorting of specific miRNAs into EVs does not play a major role in enhancing CRC proliferation [291]. Thus, the authors provided evidence that amphiregulin, transported by EVs, is a major factor in inducing CRC proliferation [291].…”
Section: Future Prospects Of Cell-free Therapy For Cancer Treatment and Challenges To Be Overcomementioning
confidence: 99%
“…In contrast, there is no major effect of tumor-derived EVs on the activation of fibroblasts [ 60 ]. Fibroblast-derived EVs induce cell proliferation (in an epidermal growth factor-dependent manner) to colorectal cancer patient-derived organoids, and the data pointed to vesicular amphiregulin as a major factor in inducing cell proliferation [ 106 ]. The EVs derived from macrophages had also an effect over tumoral cells, and the effect increases when the release of EVs is induced by deoxycholic acid treatment.…”
Section: Evs-mediated Crosstalk Between the Tumor And Cellular Matmentioning
confidence: 99%